Understanding the needs and perspectives of ovarian cancer patients when considering PARP inhibitor maintenance therapy: Findings from two online community events - Karen A. Monuszko; Laura J. Fish; Dorinda Sparacio; Christina Lizaso; Kathryn Burn; Natalie E. Wickenheisser; Larissa A. Meyer; Shelby D. Reed; Brittany A. Davidson; Laura J. Havrilesky (Elsevier, 2022)
Objective: The online environment is an ideal setting to understand how many women seek, receive, and understand information about cancer treatment. The purpose of this study was to understand women's needs and information-seeking around Poly ADP ribose polymerase (PARP) inhibitors, an oral medication commonly prescribed as maintenance therapy at the conclusion of primary chemotherapy for ovarian cancer. Methods: We held online discussion events with two social media communities, #gyncsm social media on Twitter and the Smart Patients ovarian cancer community, in November 2020, to sample ovarian cancer patient perceptions of, and information seeking about PARP inhibitors. Focused questions were presented to both communities, with participants able to answer and elaborate upon these questions, as well as to add their own comments or topics. Qualitative content analysis was performed on the transcripts from the two online events. Results: A total of 254 unique tweets and 71 messages were generated from the Twitter and Smart Patients conversations, respectively. The majority of the content from these two events could be categorized into five major themes: (1) concerns about side effects, (2) expectations of benefit, (3) desire for more information regarding clinical trials, ) (4) desire to better understand the relationship between mutation status and PARP inhibitor effectiveness, and (5) financial toxicity. Misinformation was rarely identified. Conclusions: Women with ovarian cancer who are engaged in online patient communities have numerous educational needs regarding PARP inhibitors. Given the complexity of clinical research on PARP inhibitors, patients would likely benefit from patient-centered educational tools.